The Effectiveness of Settlement of Criminal Acts of Minors Through Non-Litigation Efforts at the Gorontalo District Court - Ismiaty Amiri (Universitas Negeri Gorontalo, 2020)
Abstract: This Reaserch aims at finding out (1) to what extent the efficacy of non-litigation, especially diversion in settlement of crimes involving children, in Gorontalo district court and (2) factors hindering the non-litigation process against crimes involving children in Gorontalo district court. The research method employs a normative and ampirical approach.Finding indicate that the implementation of non-litigation in settlement of crimes involving children in Gorontalo district court is less effective. This is due to the externalities existing on the child who is referred to as a perpetrator or victim’s parent/guardian. Hence, a thorough education outreach needs to be conducted to the family and the children regarding the objectives and the benefits of the diversion. Key words : Crimes Involving children, Non-Litigation, Diversion